Rice Production Under Different Water Input - Jahan, Md Sarwar (2004)
“More crops per drop” concept is a growing interest in rice cultivation. An experiment was carried out to determine the effect of reducing water on rice production and to investigate the temporal changes in chemical properties in soil solution. There were five treatments simulating different flooding depths and durations during the rice growing period namely, W1: continuous flooding at 5cm, W2: continuous flooding at 1cm, W3: continuous flooding at 5 cm for the first 3 weeks followed by 1cm thereafter, W4: continuous flooding at 5 cm for the first 6 weeks followed by 1cm thereafter, and W5: continuous flooding at 5cm for the first 9 weeks followed by 1cm thereafter. Soil pH and redox potential were taken at 4cm depth, and the concentrations of N, P, K, Ca, Mg, Zn, Cu, Fe, and Mn in soil solution were measured at weekly intervals. At harvest, the number of tillers and panicles were counted. Grain yield, number of grains per panicle and weight of 1000 seeds were determined. In addition, the weight of straw was also obtained. The effect of irrigation treatments was not significant for tiller number, panicle number, grain yield (t/ha), straw weight (t/ha), grain/panicle, and 1000 seeds weight (g).The tiller numbers and panicle numbers were in the range of 6745000 to 6956000, and 6367000 to 6651000 per ha, respectively. Grain yield of rice under continuous 5cm flooding was not significantly different from the other treatments. Dry filled grain yield (12% moisture content) was found to range from 11.72 to 12.39 t/ha. The weight of 1000 seeds was 27.2 to 27.8g. The different flooding levels had no significant effect on the nutrients concentration analyzed in soil solution at weekly intervals. However, in general, there was an increase in the concentrations of N, Zn, Cu, Fe, and Mn in the soil solution during the first few weeks of flooding, then the values remained relatively stable until harvest, while P concentration remained constant through out the growing period in all treatments. The concentration of K, Ca, and Mg declined with time for all treatments. Redox potential value was significantly lower in treatments that were under 5cm flooding water compared to 1 cm flooding water, and it showed values that were more negative. Soil pH was in the range of 5.4 to 6.6 in all treatments. Overall, this study showed that yield and yield components, nutrient concentration, and soil pH were not affected by different water treatments but redox potential was significantly different.